2010
DOI: 10.1111/j.1475-6811.2010.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Premarital affect as a predictor of postnuptial marital satisfaction

Abstract: Although well established with newlywed couples, studies examining the association between affective communication during conflict and later relationship satisfaction yield inconsistent results with premarital samples. The current study reexamined this association with a different method of coding affect observed during discussions of separate male‐ and female‐selected problem topics and contemporary methods for modeling dyadic data. The sample included 32 engaged couples assessed across the transition to marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
(65 reference statements)
2
9
0
Order By: Relevance
“…Nevertheless, greater conflict pertaining to men's alcohol was also predictive of subsequent declines in intoxication frequency over time, with a similar effect emerging for baseline conflict pursuant to women's use on decreased frequencies of conjoint intoxication. These latter findings imply that conflict pertaining to alcohol use may have served a corrective function for these couples in the long run, which dovetails with more general evidence that conflict within intimate relationships is not always bad (e.g., Mattson, Frame, & Johnson, 2011). However, research also indicates that negative social control typically has the opposite effect on health-related behavioral change (e.g., Tucker & Anders, 2001), which may indicate that something specific to the present investigation (e.g., that men were already trying to control their drinking) may contextualize or otherwise account for these effects.…”
Section: Differential Intoxicationsupporting
confidence: 63%
“…Nevertheless, greater conflict pertaining to men's alcohol was also predictive of subsequent declines in intoxication frequency over time, with a similar effect emerging for baseline conflict pursuant to women's use on decreased frequencies of conjoint intoxication. These latter findings imply that conflict pertaining to alcohol use may have served a corrective function for these couples in the long run, which dovetails with more general evidence that conflict within intimate relationships is not always bad (e.g., Mattson, Frame, & Johnson, 2011). However, research also indicates that negative social control typically has the opposite effect on health-related behavioral change (e.g., Tucker & Anders, 2001), which may indicate that something specific to the present investigation (e.g., that men were already trying to control their drinking) may contextualize or otherwise account for these effects.…”
Section: Differential Intoxicationsupporting
confidence: 63%
“…72,73 Both frequent substance use and comorbid psychological problems are risk factors for the development of SUDs. 16,74,75 In addition, maladaptive psychological symptoms or substance use may undermine the choice of an appropriate partner 76,77 or evoke withdrawal, anger, aggression, or impaired interpersonal skills (e.g., in communication and conflict resolution) [78][79][80][81] that adversely affect the spousal/partner relationship.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth considering whether relationship satisfaction between dating couples can predict the quality of their subsequent marital experience. A study by Mattson, Frame, and Johnson () found that how people feel about their current relationship can predict their affection after marriage. Particularly in Indonesia, some couples may be resistant to ending an unsatisfactory relationship due to strong family pressure to marry their current partner or to accept a parentally arranged marriage (Utomo, ).…”
Section: Correlation Of Jealousy and Relationship Satisfaction Betweementioning
confidence: 99%